2014
DOI: 10.1007/s00127-014-0951-8
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness mediates the relationship between childhood trauma and adult psychopathology: evidence from the adult psychiatric morbidity survey

Abstract: Childhood abuse (CA) has been found to be related to the development of a variety of psychiatric disorders in adulthood. Although CA is also associated with adult loneliness, few studies have investigated the role of loneliness as a mediator in the relationship between CA and adult psychopathology. Using data from a large, general population sample a mediation model was proposed and tested. Controlling for a range of background variables, the results from a series of regression analyses found that loneliness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 68 publications
10
89
4
1
Order By: Relevance
“…It might also be that a history of depression already influences the size of a social network as well as loneliness in adulthood, which increases the vulnerability for (another) depression. Our findings are in line with those of Shevlin et al, 33 who showed, in a sample of women with a mean age of 51 years, that loneliness mediated the association between childhood abuse and adult psychopathology including depression. However, to our knowledge, our study is the first that considered social network size or loneliness in late-life depression, differentiating between an early onset and a late onset.…”
Section: Discussionsupporting
confidence: 93%
“…It might also be that a history of depression already influences the size of a social network as well as loneliness in adulthood, which increases the vulnerability for (another) depression. Our findings are in line with those of Shevlin et al, 33 who showed, in a sample of women with a mean age of 51 years, that loneliness mediated the association between childhood abuse and adult psychopathology including depression. However, to our knowledge, our study is the first that considered social network size or loneliness in late-life depression, differentiating between an early onset and a late onset.…”
Section: Discussionsupporting
confidence: 93%
“…Depression and anxiety therefore acted as mediators in this model. If Model 4 was an improvement over Model 1 (where the a and b paths of this indirect effect are fixed to zero) this would provide evidence of a mediation effect (Shevlin et al, 2015;Wickham et al, 2014). Model 4 was a substantial improvement over Model 1, ΔAIC¼ À394.37.…”
Section: Do Affective Symptoms Mediate the Relationship Between Affecmentioning
confidence: 95%
“…Researchers have suggested that demographic variables (e.g., gender) are predictive of loneliness experiences, but results in this area are inconsistent on whether loneliness is more prevalent in men (Dykstra & de Jong Gierveld, 2004) or women (Jakobsson & Hallberg, 2005). More recently, researchers have examined instances of trauma and their role in one's experiences of loneliness (e.g., Shevlin, McElroy, & Murphy, 2015;Solomon, Bensimon, Greene, Horesh, & Ein-Dor, 2015).…”
Section: Sources Of Lonelinessmentioning
confidence: 99%